2007
DOI: 10.1007/s10750-007-0593-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential for the development of submerged macrophytes in eutrophicated shallow peaty lakes after restoration measures

Abstract: Biomanipulation of eutropicated peaty lakes has rarely been successful; clear water with dense macrophyte stands fails to develop in most cases. It was unclear whether (1) high turbidity due to resuspension by benthivorous fish or wind is the major cause of low macrophyte density or whether (2) the establishment of submerged macrophyte stands is prevented by a lack of propagules, low cohesive strength of the lake sediment, high concentrations of phytotoxics, grazing by waterfowl and/or shading by periphyton gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…7) charophytes cooccurred with Ceratophyllum demersum within the stands dominated by this common macrophyte. Available in literature data seem to confirm our findings indicating that charophytes can occur in Ceratophyllum demersum stands when they have favorable growth conditions (Lehmann & Lachavanne, 1999;Tracy et al, 2003;Mäemets & Freiberg, 2005;Bazarova & Itigilova, 2006;Kłosowski, 2006;van de Haterd & Ter Heerdt, 2007;Kraska, 2009;Pełechaty et al, 2009;Gąbka et al, 2010). Fig.…”
Section: Discussionsupporting
confidence: 88%
“…7) charophytes cooccurred with Ceratophyllum demersum within the stands dominated by this common macrophyte. Available in literature data seem to confirm our findings indicating that charophytes can occur in Ceratophyllum demersum stands when they have favorable growth conditions (Lehmann & Lachavanne, 1999;Tracy et al, 2003;Mäemets & Freiberg, 2005;Bazarova & Itigilova, 2006;Kłosowski, 2006;van de Haterd & Ter Heerdt, 2007;Kraska, 2009;Pełechaty et al, 2009;Gąbka et al, 2010). Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The question whether herbivores can prevent the colonisation of macrophytes in restored shallow water bodies is debated. Experiments where macrophytes were transplanted in restored lakes showed that herbivores (large fish and waterfowl) strongly reduced macrophyte biomass (Lauridsen et al, 1993;Sondergaard et al, 1996;Lauridsen et al, 2003b;Irfanullah & Moss, 2004;Van de Haterd & Ter Heerdt, 2007;Moore et al, 2010). However, Perrow et al (1997) and Strand & Weisner (2001) found no significant reduction due to herbivory by fish and birds in restored lakes of the biomass of macrophytes that had developed spontaneously, whereas Hilt (2006) found a more than 90% reduction of P. pectinatus vegetation through grazing.…”
Section: Herbivory On Returning Macrophytesmentioning
confidence: 99%
“…In lakes where sediment contributes most to water turbidity and sediment dynamics prevent macrophyte recruitment, the creation of shelter and removal of sediment disturbing fish will be necessary; as shown by lake biomanipulation studies (Gulati & Van Donk, 2002;Sondergaard et al, 2007;Gulati et al, 2008). When optimal light conditions are re-established, plants can respond fast by germination and colonisation of the shallow water body (Van de Haterd & Ter Heerdt, 2007). However, whereas biomanipulation can initially result in a strong expansion of macrophyte vegetation, which can be species rich, the community often rapidly changes and becomes dominated by eutrophic species.…”
Section: Restoration Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The submerged vegetation increased to 30%. In another report [116] 60% coverage in shallow areas was observed. Rao et al [87] reported that larger Tilapia should be selectively harvested because the large Tilapia fed on macrophytes while small Tilapia fed on periphyton, seston, and detritus.…”
Section: Biological Methodsmentioning
confidence: 85%